Letter from Marianne Homburger to Max Bredig, May 12, 1939 - Homburger, Marianne (1939)
Marianne Homburger (1903-1987) informs her brother, Max Bredig (1902-1977), that her stepchildren have left for England on a Kindertransport and are currently attending schools in Eastbourne. She next mentions that she has submitted a visa request to England for their father, Georg Bredig (1868-1944), and that a similar application for herself and her husband, Viktor Homburger (1888-1968), is progressing well, but they need to be prepared for any outcome. She concludes by wishing Max well in New York and extending regards to his girlfriend, Liselotte.
Keywords: Homburger, Marianne, 1903-1986; Bredig, Max Albert, 1902-1977; Jewish Holocaust (1939-1945); Emigration and immigration; Kindertransports (Rescue operations)